Pengaruh Debt to Equity Ratio dan Arus Kas Operasi terhadap Kinerja Keuangan Perusahaan Transportasi dan Logistik - Aribah, Lutfiah; Jamal, Sri Wahyuni; Pribadi, Muhammad Iqbal (Pustaka Peradaban, 2025)
The transportation and logistics sector plays a strategic role in supporting the distribution of goods and services as well as sustaining national economic growth. This study aims to examine the effect of the debt to equity ratio (DER) and operating cash flow on the financial performance of transportation and logistics companies listed on the Indonesia Stock Exchange (IDX) during the 2013–2024 period. Data were obtained from annual financial reports selected using a purposive sampling technique and analyzed with multiple linear regression. The results reveal that DER has no significant effect on financial performance, while operating cash flow shows a significant positive effect. These findings provide theoretical implications by strengthening the financial accounting literature, emphasizing that operating cash flow is a more relevant indicator of financial performance than capital structure ratios such as DER, particularly in the transportation and logistics sector. From a practical perspective, the results suggest that company management should prioritize strategies to optimize operating cash flow, while investors are encouraged to use operating cash flow as a key indicator when assessing the financial health of companies in this sector. Sektor transportasi dan logistik memiliki peran strategis dalam mendukung distribusi barang dan jasa serta menopang pertumbuhan ekonomi nasional. Penelitian ini bertujuan menganalisis pengaruh debt to equity ratio (DER) dan arus kas operasi terhadap kinerja keuangan perusahaan transportasi dan logistik yang terdaftar di Bursa Efek Indonesia (BEI) periode 2013–2024. Data diperoleh melalui laporan keuangan tahunan perusahaan yang dipilih dengan teknik purposive sampling dan dianalisis menggunakan regresi linier berganda. Hasil penelitian menunjukkan bahwa DER tidak berpengaruh signifikan terhadap kinerja keuangan, sedangkan arus kas operasi berpengaruh signifikan. Temuan ini memiliki implikasi teoretis dengan memperkuat literatur akuntansi keuangan mengenai dominasi arus kas operasi dibandingkan rasio struktur modal dalam menjelaskan kinerja keuangan. Dari sisi praktis, hasil penelitian ini memberikan masukan bagi manajemen perusahaan untuk memprioritaskan strategi peningkatan arus kas operasi, serta bagi investor dalam menilai kesehatan finansial perusahaan di sektor transportasi dan logistik.